Vontade e contravontade em Confissões, VIII, de Agostinho - Silva, João Paulo da (2023)
The aim of this dissertation is to analyze the division of the will in Augustine's Confessions, VIII, considering it a fundamental concept in Augustinian philosophy. The argumentative path taken in Book VIII regarding conversion leads Augustine to recognize the autonomy of the human will. In this context, the will plays a crucial role in driving human pursuit of happiness, attainable only in communion with God. However, Augustine understands that the human will is tainted by original sin, resulting from Adam's fall. The fall introduced sin into human nature, corrupting it and inclining it towards evil. Thus, the human will is divided between the desire to seek the good (good will) and the desire to succumb to temptations and sinful inclinations (bad will). These two opposing wills divide the human soul and establish a universal and unconditional internal conflict, which can only be overcome through appeasement of conflicting desires within the soul and liberation through grace (that is, through divine initiative rather than human) from perverse habits that shackle the will